2017
DOI: 10.3846/bme.2017.358
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Stock Price Overreaction and Investor Overconfidence Issues

Abstract: This research examines the existing of investor overconfidence in the capital market and the phenomena of stock prices reversal in the future due to the existing of this behavior. It has a different approach to test the existing of investor overconfidence by introducing firm’s growth as the information which has triggered many investors to behave overconfidently. By using multiple regression analysis, the results of this research confirmed our conducted hypothesis, investor tends to behave overconfident to fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This result is in line with several previous studies that state that female and male have different behaviors in purchase decision (Bashir et al , 2013; Hassan, 2015; Ma et al , 2012; Michon et al , 2008; Mittal, 2019; Mokoena and Maziriri, 2017; Nayebzadeh and Jalaly, 2014; North et al , 2003; Rajput et al , 2012; Rao et al , 2018; Sheth, 1974; Zhuang et al , 2006). Raharja et al (2017) pinpoint that men tend to be spontaneous in product purchasing. Meanwhile, women always consider many aspects at the time of purchasing and so require a long time to become loyal consumers.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with several previous studies that state that female and male have different behaviors in purchase decision (Bashir et al , 2013; Hassan, 2015; Ma et al , 2012; Michon et al , 2008; Mittal, 2019; Mokoena and Maziriri, 2017; Nayebzadeh and Jalaly, 2014; North et al , 2003; Rajput et al , 2012; Rao et al , 2018; Sheth, 1974; Zhuang et al , 2006). Raharja et al (2017) pinpoint that men tend to be spontaneous in product purchasing. Meanwhile, women always consider many aspects at the time of purchasing and so require a long time to become loyal consumers.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is consistent with several previous studies that found trust to be a critical factor affecting the intention to behave. For instance, consumers were observed to make a purchasing decision when they trust a product (Bonsón Ponte et al, 2015;Chinomona et al, 2013;Raharja et al, 2017;Sethna et al, 2017;Weisberg et al, 2011). Therefore, as an official partner in the forthcoming mass COVID-19 vaccination program, the government must pay more attention to establishing public trust to ensure the successful completion of the program.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the information they are preview to, investors tend to believe that they know more. They found on knowledge and skills and disregarded the risk associated with the investment (Raharja et al, 2017). Overconfidence bias has a significant favourable influence on investment decisions (Subash, 2012).…”
Section: Overconfidence Biasmentioning
confidence: 99%